Pengaruh Kompetensi Dan Motivasi Terhadap Kinerja Karyawan Melalui Kepemimpinan: Suatu Kajian Perspektif Karyawan PT Assab Steels Indonesia - Febyanti, Leily; Wicaksana, Seta A; Putriana, Lies (CV ODIS, 2024)
The Problems identified in this research are How is the partial and direct influence of competence on leadership, How is the partial and direct influence of motivation on leadership? Then, how does the partial and direct effect of competence on employee performance, How does the partial and direct effect of motivation on employee performance? Then how is the influence of leadership as a moderator of the indirect relationship between competence and motivation on the performance of employees of PT Asaab Steel Indonesia? This research approach was carried out through a survey, and each problem raised to the surface was carried out through an Explanatory Analysis, namely explaining the causality relationship between echogenic and endogenous variables through direct and indirect PATH analysis models using standardized coefficient data. beta. Through 79 employees or representative respondents used as research samples obtained the findings of al: Partially and direct competence has a positive and significant effect on leadership; Partially and direct motivation has a positive and relatively weak effect, but significant to leadership; Partially and directly competence has a positive and relatively weak effect, but significant to employee performance; Partially and directly motivation has a positive and relatively weak effect, but significant to employee performance; Indirectly leadership is capable of being a strong and significant moderator between competency and motivation on the performance of employees of PT.Assab Steel Indonesia.